2020
DOI: 10.1108/jsma-03-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

The influence of CEO duality and board size on the market value of spun-off subsidiaries

Abstract: PurposeCorporate spin-offs have become more popular as a restructuring technique in recent decades. The market performance of these spun-off subsidiaries has been considered critical, as positive market signals are vital to the success of these newly independent firms. Drawing on both the stewardship and resource dependence theories, this study aims to examine how two critical governance characteristics (namely, CEO duality and board size) affect the change in the market valuation of spun-off subsidiaries. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 84 publications
(79 reference statements)
0
25
0
1
Order By: Relevance
“…Prior literature concluded that the board size is one of the important mechanisms of corporate governance (Buachoom, 2018;Bzeouich et al, 2019;Merendino & Melville, 2018;Ozbek & Boyd, 2020;Shahid et al, 2020). Agency theory agrees with resource dependency theory regarding the positive effect of board size on firm performance.…”
Section: Board Size and Firm Performancementioning
confidence: 68%
See 1 more Smart Citation
“…Prior literature concluded that the board size is one of the important mechanisms of corporate governance (Buachoom, 2018;Bzeouich et al, 2019;Merendino & Melville, 2018;Ozbek & Boyd, 2020;Shahid et al, 2020). Agency theory agrees with resource dependency theory regarding the positive effect of board size on firm performance.…”
Section: Board Size and Firm Performancementioning
confidence: 68%
“…Likewise, Carty and Weiss (2012) documents no correlation between CEO duality and firm performance. Although the empirical evidence on the relationship between CEO duality and firm performance is still inconclusive, the stewardship theory argues that when one person holds all power at the top level, major conflicts would be avoided during the decision-making cycle (Ozbek & Boyd, 2020). Thus, the following hypothesis is then proposed: H4a: There is a positive relationship between CEO duality and ROA.…”
Section: Ceo Duality and Firm Performancementioning
confidence: 99%
“…Thus, CEOs with multiple positions can weaken the organizational monitoring structure and negatively affect company performance (Chatterjee, 2020). Uppal (2020) and Ozbek & Boyd (2020) state that CEOs with multiple positions can reduce CEO independence and worsen company performance. Chychyla et al (2019) and Salehi et al (2020) show that companies with a worse performance show that the company annual report is longer and more complicated than companies with a good performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Empirical evidence has proven a possible trade-off between costs and benefits of conversing additional decision-making power with CEOs (Chatterjee & Hambrick, 2011). One school of thought associates CEO power with firm's efficiency as he can accelerate the decision-making processes, resulting in timely responses to the market (Ozbek & Boyd, 2020).…”
Section: Introductionmentioning
confidence: 99%